Atypical manifestations in a patient with systemic lupus erythematosus. Issue 2 (February 1997) - Lam, K Y; Cheung, F; Yam, L Y; Lee, C H; Fung, K H
Abstract : Systemic lupus erythematosus (SLE) is a chronic systemic inflammatory disease associated with the production of various autoantibodies and involvement of multiple organs. Necropsy findings in a 65 year old woman with SLE who had multiple aortic aneurysms and dissections, as well as other unusual manifestations, are described. The case illustrates the occurrence of and the difficulties encountered in the diagnosis of several diseases, namely aortic aneurysm, aortic dissection, acute pancreatitis, and Penicillium marneffei infection.